Analisis Pengaruh Profitabilitas Dan Rasio Pasar Terhadap Harga Saham Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Veronica Veronica; Erni Yanti Natalia (eCo-Buss, 2022)
This study aims to determine the variable ROE, ROA and EPS of the company’s stock price that is listed on the Indonesian Stock Exchange (BEI) 2016-2020. The population in this study were company’s industry subsector food and beverage. This study were using purposive sampling method.The result of this study showed that ROE and ROA does not effect the Stock Price with a significance level of 0,610 where 0,610 > 0,05 and has t of t count 0,513 < 2,013 and variabel ROA 0,549 where 0,549 > 0,05 and has t of t count 0,603 < 2,013 negative direction. EPS is partially a significant positive effect with a significance level of 0,000 where 0,000 < 0,05 and t count 8,390 > 2,013 positive direction and simultaneously the ROE, ROA and EPS together a significant effect on the stock price with a significant value of 0,000 < 0,05 and F count is found to be 41,547 while F table is equal to 2,807 or 41,547 > 2,807. Value adjusted R Square of 0,713 means that the stock price variable variation can be explained by the variable is 71,3% and 28,7% is explained by other variables not included in the research model